CAMPUR KODE PADA NOVEL LAUT BERCERITA KARYA LEILA S. CHUDORI PERSPEKTIF PRAGMATIK - Linda Eka Pradita (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
Language is the most important aspect in the formation of values ??in a literary work. The use of language in each literary work is different. This depends on the culture that is raised in literary works. Not only Indonesian is used, but there are also Indonesian literary works that contain foreign languages ??or regional languages. This research focuses on code mixing in Leila S. Chudori's novel Laut Bercerita by using a pragmatic perspective. Some literary works use more than one language. This study aims to obtain a description that includes forms of code mixing from several languages. By using the observation method and note-taking techniques, this study was analyzed using a pragmatic approach. Based on this, syntactically the form of word insertion code mixing is produced, phrase insertion, and insert clauses loaded in the data. Keywords: language, code mixing, syntax, pragmatics